2018
DOI: 10.1590/0103-8478cr20160066
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of Chinese southwest wheat germplasms resistant to stripe rust and powdery mildew using the DArT-seq technique

Abstract: Understanding genetic variability in existing wheat accessions is critical for collection, conservation and use of wheat germplasms. In this study, 138 Chinese southwest wheat accessions were investigated by genotyping using two resistance gene makers (Pm21 and Yr26) and DArT-seq technique. Finally, about 50% cultivars (lines) amplified the specific allele for the Yr26 gene (Gwm11) and 40.6% for the Pm21 gene (SCAR1265). By DArT-seq analysis, 30,485 markers (6486 SNPs and 23999 DArTs) were obtained with mean p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…Polymorphic information content (PIC) values revealed by DArTseq markers averaged 0.165 with an asymmetric distribution skewed towards low values. The same distribution tendency was found using the same approach for 91 durum wheat landraces from the Fertile Crescent and for 138 wheat germplasm from Southwest China [32,41]. Ren et al [43] have shown the same PIC value for North African durum accessions (0.168) using 946 SNP markers as part of a genetic diversity study in a worldwide durum wheat germplasm collection.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Polymorphic information content (PIC) values revealed by DArTseq markers averaged 0.165 with an asymmetric distribution skewed towards low values. The same distribution tendency was found using the same approach for 91 durum wheat landraces from the Fertile Crescent and for 138 wheat germplasm from Southwest China [32,41]. Ren et al [43] have shown the same PIC value for North African durum accessions (0.168) using 946 SNP markers as part of a genetic diversity study in a worldwide durum wheat germplasm collection.…”
Section: Discussionsupporting
confidence: 60%
“…The large coverage of the genomes can serve to undertake association mapping in the studied germplasm, including finding new allelic variations for major breeders sought traits such as QTLs found by other studies in chromosomes 7A and 2B linked to protein content [36], gluten strength and yellow pigment [37,38], and salinity tolerance and yield components [39,40]. DArTseq technology along with other high throughput and genotyping by sequencing molecular techniques are increasingly used to study the genetic diversity of different crops as they allow to study the genetic diversity of large number entries and complex genomes [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Among the three sub-genomes, the mean PIC for the D sub-genome (0.14) was slightly lower than that of the A or B sub-genomes (0.16) ( Table 1 ) due to limited hybridization event and gene flow in Aegilops tauschii during evolution ( Chao et al, 2009 ; Lopes et al, 2015 ; Liu Y. et al, 2017 ; Eltaher et al, 2018 ; Tyrka et al, 2021 ). However, much higher PIC (0.26–0.33) were reported in other studies ( Allen et al, 2013 ; Baloch et al, 2017 ; Chen et al, 2018 ; Kumar et al, 2020 ; Yang et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 51%
“…Wide-genome genotyping of the 439 inbred lines was conducted using DArTseq technology [ 21 , 40 ]. Following a strict quality control process involving parameters such as call rate, data reproducibility (~ 20% of samples replicated), and rate of monomorphism to remove monomorphic markers, 18,927 SNPs were obtained from the studied germplasm.…”
Section: Methodsmentioning
confidence: 99%